Paired analysis of host and pathogen genomes identifies determinants of human tuberculosis - Luo, Y; Huang, C; Howard, NC; Wang, X; Liu, Q; Li, X; Zhu, J; Amariuta, T; Asgari, S; Ishigaki, K; Calderon, R; Raman, S; et al. (Nature Research, 2024)
Infectious disease is the result of interactions between host and pathogen and can depend on genetic variations in both. We conduct a genome-to-genome study of paired human and Mycobacterium tuberculosis genomes from a cohort of 1556 tuberculosis patients in Lima, Peru. We identify an association between a human intronic variant (rs3130660, OR = 10.06, 95%CI: 4.87 − 20.77, P = 7.92 × 10−8) in the FLOT1 gene and a subclavaluee of Mtb Lineage 2. In a human macrophage infection model, we observe hosts with the rs3130660-A allele exhibited stronger interferon gene signatures. The interacting strains have altered redox states due to a thioredoxin reductase mutation. We investigate this association in a 2020 cohort of 699 patients recruited during the COVID-19 pandemic. While the prevalence of the interacting strain almost doubled between 2010 and 2020, its infection is not associated with rs3130660 in this recent cohort. These findings suggest a complex interplay among host, pathogen, and environmental factors in tuberculosis dynamics.